2021
DOI: 10.1111/acfi.12748
|View full text |Cite
|
Sign up to set email alerts
|

MD&A readability, auditor characteristics, and audit fees

Abstract: This paper investigates the relationship between audit fees and MD&A readability in China. We find that audit fees generally are higher when MD&A readability is lower. However, we find Big4 auditors and industry specialist auditors do not increase audit fees when MD&As are less readable while the other auditors do. We also find that it is the content unique to the reporting firm, rather than standard industry and market content in a MD&A that affects auditor fees. Our results also support that audit risk and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 35 publications
(90 reference statements)
0
11
0
2
Order By: Relevance
“…Research by Ege and Stuber (2022) which states that one of the causes of auditor failure in detecting fraud is the low level of audit skepticism. As well as research conducted by Wang et al (2021), showing that auditors with a combination personality type "sensing-thinking" and "intuitivethinking" show a higher professional sceptic thinking in detecting fraud, compared to auditors with other personality types.…”
Section: The Effect Of Professional Skepticism In Financial Statementmentioning
confidence: 67%
“…Research by Ege and Stuber (2022) which states that one of the causes of auditor failure in detecting fraud is the low level of audit skepticism. As well as research conducted by Wang et al (2021), showing that auditors with a combination personality type "sensing-thinking" and "intuitivethinking" show a higher professional sceptic thinking in detecting fraud, compared to auditors with other personality types.…”
Section: The Effect Of Professional Skepticism In Financial Statementmentioning
confidence: 67%
“…By using the readability of MD&A in the WinGo database, Wang et al. (2021) found that firms are charged higher audit fees when their MD&A readability is lower. Hu et al.…”
Section: Methodsmentioning
confidence: 99%
“…‫باح‬ ‫األر‬ ‫ة‬ ‫إدار‬ ‫و‬ ‫المستقبلي‬ ‫األداء‬ ‫مثل:‬ ‫التمويل‬ ‫و‬ ‫المحاسبة‬ ‫ات‬ ‫متغير‬ ‫من‬ ‫كبير‬ ‫عدد‬ ‫على‬ ‫اءة‬ ‫للقر‬ (Ajina et al, 2016;Li, 2008) ‫االستثمار‬ ‫وكفاءة‬ ، (Biddle et al, 2009) ‫الماليين‬ ‫المحللين‬ ‫وسلوك‬ ، (Aymen et al, 2018;Lehavy et al, 2011) ‫األسهم‬ ‫في‬ ‫ين‬ ‫للمستثمر‬ ‫التداول‬ ‫وسلوك‬ ، (Lawrence, 2013;Miller, 2010) ‫باح‬ ‫باألر‬ ‫التنبؤ‬ ‫أخطاء‬ ‫و‬ ‫ائد‬ ‫العو‬ ‫وتقلب‬ ، (Loughran & McDonald, 2014) ‫األسهم‬ ‫أسعار‬ ‫انهيار‬ ‫وخطر‬ ، (Kim et al, 2019) ‫المعلومات‬ ‫تماثل‬ ‫وعدم‬ ، (Dalwai et al, 2021;Luo et al, 2018 (Bloomfield, 2008;Gosselin et al, 2021;Li, 2008;Lo et al, (Courtis, 1987(Courtis, , 1995Jang & Rho, 2016;Li, 2008 (Ayuningtyas & Harymawan, 2021;Ertugrul et al, 2017;Fang-Klingler, 2019;Hoffmann & Kleimeier, 2021 (Abernathy et al, 2019;Blanco et al, 2021;Salehi et al, 2020;Wang et al, 2021;Xu et al, 2020b (Bloomfield, 2008;Gosselin et al, 2021;Li, 2008;Lo et al, 2017) : (Ayuningtyas & Harymawan, 2021;Courtis, 1995;De Franco et al, 2015;Ferri et al, 2022;Hassan et al, 2019;…”
Section: ‫ملخص‬ ‫البحث‬unclassified